2022
DOI: 10.1152/ajpheart.00394.2022
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia briefly increases diuresis but reduces plasma volume by fluid redistribution in women

Abstract: We have recently reported that hypobaric hypoxia (HH) reduces plasma volume (PV) in men by decreasing total circulating plasma protein (TCPP). Here, we investigated whether this applies to women and whether an inflammatory response and/or endothelial glycocalyx shedding could facilitate the TCCP reduction. We further investigated whether acute HH induces a short-lived diuretic response that was overlooked in our recent study, where only 24-h urine volumes were evaluated. In a strictly controlled crossover prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“… 37 ). Additionally, some of the body weight loss may have reflected the loss of fat-free mass (FFM) including body water, although the latter must have been minimal, given that as reported elsewhere ( 22 ), 24-h urine volumes were almost identical between sojourns (2,135 ± 142 vs. 2,130 ± 153 mL/day, for NX and HH, respectively P = 0.915), and changes in total body water throughout the sojourns were minimal (−0.108 liters vs. 0.003 liters in HH and NX, respectively; P = 0.347 n = 8) in our participants. Finally, intestinal malabsorption could have contributed to a negative energy balance in HH, although this seems unlikely as malabsorption is only described at much higher altitudes ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 37 ). Additionally, some of the body weight loss may have reflected the loss of fat-free mass (FFM) including body water, although the latter must have been minimal, given that as reported elsewhere ( 22 ), 24-h urine volumes were almost identical between sojourns (2,135 ± 142 vs. 2,130 ± 153 mL/day, for NX and HH, respectively P = 0.915), and changes in total body water throughout the sojourns were minimal (−0.108 liters vs. 0.003 liters in HH and NX, respectively; P = 0.347 n = 8) in our participants. Finally, intestinal malabsorption could have contributed to a negative energy balance in HH, although this seems unlikely as malabsorption is only described at much higher altitudes ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…The experiments were conducted as part of a project investigating different physiological effects of 4 days of hypoxia in women ( 22 ). Participants completed two 4-day sojourns in a hypobaric chamber (terraXcube, Bolzano, Italy), with barometric pressure either unmodified [normoxia (NX), P B = 761 mmHg, 262 m] or reduced to the equivalent of ∼3,500-m altitude [hypobaric hypoxia (HH), P B = 493 mmHg).…”
Section: Methodsmentioning
confidence: 99%
“…Third, the protective effect of the administration of modified hemoglobin on altitude sickness at higher altitudes was not observed. Fourth, Siebermann [ 28 ] et al. demonstrated that modified hemoglobin in humans could lead to transient diuresis at high altitudes and further investigation in this regard is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Increased solar radiation places additional heat on the surface of the body, while wind increases heat transfer from the body surface, but also increases the insensible loss of water from exposed skin (88,90). Higher altitude corresponds to lower mean ambient temperature and lower atmospheric (barometric) pressure, possibly inducing a hypoxic-mediated increase in urine volume (89,91,92). The interplay between the different variables is extensive and we have not found any fully satisfying modelling of the effect of climate on human water loss in our literature review, the study of Yamada et al being the closest (87).…”
Section: Justification Of Co-variate Selectionmentioning
confidence: 99%